Epistatic effects of Siglec-G and DNase1 or DNase1l3 deficiencies in the development of systemic lupus erythematosus - Korn, Marina; Steffensen, Marie; Brandl, Carolin; Royzman, Dmytro; Daniel, Christoph; Winkler, Thomas; Nitschke, Lars (Frontiers in Immunology, 2023)
Systemic lupus erythematosus (SLE) is a severe autoimmune disease that displays considerable heterogeneity not only in its symptoms, but also in its environmental and genetic causes. Studies in SLE patients have revealed that many genetic variants contribute to disease development. However, often its etiology remains unknown. Existing efforts to determine this etiology have focused on SLE in mouse models revealing not only that mutations in specific genes lead to SLE development, but also that epistatic effects of several gene mutations significantly amplify disease manifestation. Genome-wide association studies for SLE have identified loci involved in the two biological processes of immune complex clearance and lymphocyte signaling. Deficiency in an inhibitory receptor expressed on B lymphocytes, Siglec-G, has been shown to trigger SLE development in aging mice, as have mutations in DNA degrading DNase1 and DNase1l3, that are involved in clearance of DNA-containing immune complexes. Here, we analyze the development of SLE-like symptoms in mice deficient in either Siglecg and DNase1 or Siglecg and DNase1l3 to evaluate potential epistatic effects of these genes. We found that germinal center B cells and follicular helper T cells were increased in aging Siglecg-/- x Dnase1-/- mice. In contrast, anti-dsDNA antibodies and anti-nuclear antibodies were strongly increased in aging Siglecg-/- x Dnase1l3-/- mice, when compared to single-deficient mice. Histological analysis of the kidneys revealed glomerulonephritis in both Siglecg-/- x Dnase1-/- and Siglecg-/- x Dnase1l3-/- mice, but with a stronger glomerular damage in the latter. Collectively, these findings underscore the impact of the epistatic effects of Siglecg with DNase1 and Dnase1l3 on disease manifestation and highlight the potential combinatory effects of other gene mutations in SLE.
CRIS-Team Scopus Importer:2023-03-31
Keywords: autoimmunity; B cell signaling; inhibitory receptors; lymphocytes; mouse models